The long run performance of secondary equity offerings on the Johannesburg Stock Exchange. Issue 5 (29th November 2018) - da Cunha, Jesse Alves; Seetharam, Yudhvir
Abstract : Purpose: Opinions have been divided on whether there is a rational explanation to the reason behind seasoned equity offerings (SEOs) or whether the explanation lies within the behavioural intricacies attributed to stock market participants. The paper aims to discuss these issues. Design/methodology/approach: This study investigates the long-run performance of firms conducting SEOs on the Johannesburg Stock Exchange (JSE) over the period of 1998–2015, by examining the return performance and operating performance of firms, along with the impact of investor sentiment on these variables. Findings: The results of this study are inconsistent with the existing literature, which argues that the long-run performance of issuing firms signalled an initial underreaction to SEOs buoyed by over-optimistic investors. Research limitations/implications: Instead, the long-run performance of issuing firms is adequately explained by the rational models centred on the risk-return framework, implying that investors are reacting swiftly to SEOs in an unbiased fashion. Originality/value: Investor sentiment does not materially influence the long-run share performance or operating performance of issuing firms, casting doubt on the ability of the market timing theory to explain the long-run performance of SEOs. The authors thus find that SEO performance cannot be explained by behavioural-based reasoning, in contrast to some asset pricing studies on the JSE which indicate the role of sentiment in explaining returns.